Moral Injury: A Health Condition We Need to Pay More Attention - Robinson, Isla (Science Insights, 2025)
Moral injury—emerging from actions, inactions, or witnessed events that transgress deeply held moral beliefs—remains an often overlooked yet profoundly consequential health condition. While initially described among military personnel, it now spans health care workers, first responders, educators, and countless others navigating ethically fraught environments. Unlike PTSD, moral injury’s core is spiritual, ethical, and emotional dissonance rather than fear. It manifests as shame, guilt, betrayal, and loss of meaning, undermining psychological well-being and professional longevity. Yet public health systems and workplaces rarely recognize or treat it with the seriousness it deserves. This opinion article argues that ignoring moral injury not only harms individuals but weakens institutions, erodes trust, and accelerates burnout. Addressing it requires cultural change, leadership accountability, trauma-informed practices, and integration of moral repair into mainstream health care. Moral injury is a public health problem hiding in plain sight, demanding urgent attention, empathy, and structural reform.